The Impact of Dropshipping Service Quality on Customer Satisfaction in Saudi Arabia: The Mediating Role of Customer Trust. A Study on E-Commerce Users - Aburub, Abdelmoti; Aburub, Abdelmoti; Aburub, Abdelmoti; Hamida, Abdel Ghaffar Ben; Khanfar, Fayiq (Journal of Posthumanism, 2025)
This study investigates how dropshipping service quality—social media, cultural, technological influences, and delivery speed—affects customer satisfaction in Saudi Arabia, with customer trust as a mediator. Using a quantitative method, data were collected from 225 e-commerce users via a structured questionnaire and analyzed with SPSS and AMOS for SEM. Results showed all four factors significantly impacted satisfaction, with technology having the strongest effect (β = 0.30, p < 0.001), followed by social media (β = 0.25), delivery speed (β = 0.22), and culture (β = 0.20). Customer trust significantly mediated the effects of social media (indirect β = 0.14) and technology (indirect β = 0.12) on satisfaction. The study extends Service Quality and Commitment-Trust Theories to dropshipping, highlighting trust and quality as key to satisfaction. Businesses should focus on tech adoption, social engagement, and building trust to boost satisfaction and loyalty.